Pattern of clinical and laboratory presentation of cerebral malaria among children in Nigeria - Tolulope O Jegede; Saheed B Oseni; John A. O Okeniyi; Bankole Peter Kuti; Samuel A Adegoke; Qasim A Salau; Emmanuel Olaseinde Bello; Temitope Oyinlola Jegede; Abiodun John Kareem; Oyeku A Oyelami; Ibitoye Bayode Samuel; Korede O Oluwatuyi; et al. (Journal of Global Infectious Diseases, 2024)
Introduction: Cerebral malaria (CM) is the most lethal form of severe malaria with high case fatality rates. Overtime, there is an inherent risk in changing pattern of presentation of CM which, if the diagnosis is missed due to these changing factors, may portend a poor outcome. Variations in the pattern of clinic-laboratory presentations also make generalization difficult. This study was, therefore, set out to report the pattern of clinical and laboratory presentation of CM. Methods: This was a cross-sectional study among children aged 6 months to 14 years admitted with a diagnosis of CM as defined by the World Health Organization criteria. A pretested pro forma was filled, and detailed neurological examination and laboratory (biochemical, microbiology, and hematology) investigations were done. P <5% was considered statistically significant. Results: Sixty-four children were recruited with a mean age of 34.9 ± 24.9 months and a male-to-female ratio of 1.9:1. There were 87.5% of under-five children. Fever (96.9%) was the major presenting feature closely followed by convulsions (92.2%). Convulsions were mainly generalized (94.9%) and multiple (76.5%). Profound coma (Blantyre coma score of 0) was present in 12.5% of cases, and the leading features on examination were fever (84.4%) and pallor (75.0%). Retinal vessel whitening (48.4%) was the most common funduscopic abnormality. Metabolic acidosis (47.9%), severe anemia (14.1%), hyperglycemia (17.2%), and hypoglycemia (7.8%) were seen among the children. Few (1.6%) had hyperparasitemia and bacteremia (3.2%). Conclusion: Early recognition of the clinical presentation and prompt management may improve the outcome of cerebral malaria.